Translation Strategy and Accuracy in Balinese Terms - Agus Darma Yoga Pratama (Pusat Kajian Bali Universitas Udayana, 2022)
This research attempts to find out the strategy used by the translator in translating Balinese terms also to explain the accuracy of the translated terms. The data used in this research were in the form of phrases in the book entitled Tigang Satua Bali by Sutjaja (2007). The data collection was done through reading and note taking techniques. The data then were analyzed using theory of translation strategy and accuracy. The result showed that the strategy used within the translation of Balinese terms into target languages (Indonesian and English) are translation by paraphrase, related word, loan phrase, and cultural substitution. Then the accuracy levels of the translation strategy are in three criteria, namely correct, misguided, and unclear.